Factors influencing customer’s decision-making towards unit trust: a study in Kota Bharu / Mohd Hazim Hamzah - Hamzah, Mohd Hazim (Bachelor Of Business Administration (Hons) Marketing, 2013)
This study attempts to determine the factors that influencing customer’s decision-making towards unit trust in Kota Bharu.This study uses primary and secondary data. 100 questionnaires was distributed to the public in Kota Bharu The data collected was then tested on the multiple regression analysis and then were use to test the hypothesis in this study. The researcher also measure how knowledge can contribute to the customer’s decision-making. Besides that, the fund performance also become independent variable in this study and it has a positive relationship with the customer’s decision-making. From this research, it’s revealed what is the most influence the customer’s decision-making towards unit trust. Researcher also suggests some recommendation to the government, issuers companies and also public